Electrochemical detection of hydrogen peroxide on a new microporous Ni–metal organic framework material-carbon paste electrode - Sherino, Bibi; Mohamad, Sharifah; Halim, Siti Nadiah Abdul; Manan, Ninie Suhana Abdul (Elsevier, 2018)
In this paper a new Ni2+ metal organic framework (based on adipic acid as the linker & piperazine as the ligand) (AP-Ni-MOF) was synthesized and has been used as an electrode material (AP-Ni-MOF/CPE) for the detection of H2O2. The morphology and formation of AP-Ni-MOF was confirmed by field emission scanning electron microscopy, FT-IR spectroscopy, energy-dispersive spectroscopy, X-ray diffraction, and TGA. AP-Ni-MOF showed high electrochemical activity for the detection of H2O2 due to high conductivity i.e 1.28 × 10−3 S/cm. Electrochemical studies were carried out for AP-Ni-MOF/CPE by cyclic voltammetry and chrono-amperometry methods. Under optimized condition AP-Ni-MOF/CPE show a dynamic range (0.004 mM to 60 mM) with the limit of detection of 0.0009 mM. The effect of interfering species on the reduction peak current response show a minor change of signals (>5%). The modified electrode has good repeatability due to lifetime stability. AP-Ni-MOF/CPE electrode was also used in real samples (lens cleaner solution) for the detection of H2O2 with the recoveries of 94.7–107%.